Congenital myasthenic syndrome secondary to pathogenic variants in the SLC5A7 gene: report of two cases - Javier A Muntadas; Martin R Hyland; Maria Del Rosario Ortolá Martínez; Jaime N Young; Jessica X Chong; Michael J Bamshad; Ricardo A. Maselli (BMC Medical Genomics, 2024)
Abstract Background Congenital Myasthenic Syndromes (CMS) are rare genetic diseases, which share as a common denominator muscle fatigability due to failure of neuromuscular transmission. A distinctive clinical feature of presynaptic CMS variants caused by defects of the synthesis of acetylcholine is the association with life-threatening episodes of apnea. One of these variants is caused by mutations in the SLC5A7 gene, which encodes the sodium-dependent HC-3 high-affinity choline transporter 1 (CHT1). To our knowledge there are no published cases of this CMS type in Latin America. Case presentation We present two cases of CHT1-CMS. Both patients were males presenting with repeated episodes of apnea, hypotonia, weakness, ptosis, mild ophthalmoparesis, and bulbar deficit. The first case also presented one isolated seizure, while the second case showed global developmental delay. Both cases, exhibited incomplete improvement with treatment with pyridostigmine. Conclusions This report emphasizes the broad incidence of CMS with episodic apnea caused by mutations in the SLC5A7 gene and the frequent association of this condition with serious manifestations of central nervous system involvement.